A study on Digital Marketing and Its Impact (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This review paper's goal is to investigate the significance of digital marketing for both consumers and advertisers. This essay starts with a brief introduction to digital marketing before focusing on the various forms it can take, the ways in which it differs from traditional marketing, as well as its advantages and disadvantages as well as its significance in the modern world. As the world transitions from analogue to digital, so does marketing. The use of digital marketing, social media marketing, and search engine marketing is growing along with the pace of technological advancement the number of internet users is raising quickly, and as digital marketing relies heavily on the internet, it has benefited the most. Consumers' purchasing habits are evolving, and they prefer digital marketing to traditional marketing.India, which is still sometimes referred to as the "nation of villages," has one of the fastest expanding economies in the entire globe. India may suddenly have a burgeoning digital marketing industry. A very high crucial growth in the field of digital marketing is predicted for a nation with a growing economy. The growth of digital marketing trends is having a very significant impact on marketing and advertising. Most business sectors in India are embracing digital marketing trade. The impact of digital marketing, consumer purchasing behavior, the significance and benefits of digital marketing, and the state of digital marketing in India will all be examined in this research paper.